The Concept Of Education Management In The Post-Conflict Regions Of West Kalimantan: A Study Of Ibn Khaldun’s Thought - Sahri Sahri (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
This article discusses the management of education in schools in the thought of Ibn Khaldun. The approach used in this study is qualitative, and the type of research is literature research. This research combines data collection techniques with document studies so that data in the form of journals and books related to Ibn Khaldun are used as primary sources in this study and refer to the work of Ibn Khaldun. The data used relates to Ibn Khaldun’s thoughts on Islamic education management. This research shows that, at least in the implementation of education management in schools, four aspects are mutually integrated: educators, students, learning materials, and learning methods. Ibn Khaldun’s perspective on educational management can be applied to educational institutions such as the Madrasah in West Kalimantan. Moreover, educational practices in West Kalimantan are still unable to overcome problems, especially in building an atmosphere of peace between students, both ethnic and religious. Educators in Madrasah, especially in West Kalimantan, can integrate learning materials with tolerance and student backgrounds without raising ethnic or religious stereotypes. The learning method can be done by understanding the material and mapping the material that can be related to building peace in West Kalimantan.